PHYSICAL AND CHEMICAL QUALITY OF CORN SILAGE WITH THE ADDITION OF LIQUID SMOKE - Andy; Aulyani, Tutik Lusyta; Dermawan; Sangkek, Miksen Merko; Arwan (Buletin Veteriner Udayana, 2024)
Processing corn plant waste into silage by adding additives is one way to improve the quality of the waste. EM4 is a microorganism that is usually used as an additive in silage making, while liquid smoke is an antibacterial and antioxidant that can prevent the growth of putrefactive bacteria. The aim of this research is to determine how the physical and chemical quality of corn plant waste silage is influenced by the addition of liquid smoke additives. This study was carried out using the Completely Randomized Design (CRD) Method. Which consisted of 4 treatments and 5 replications to obtain 20 experimental units. Testing of 4 treatment groups, namely P0: EM4 2%, P1: Liquid Smoke 2%, P2: Concentration of 1% Liquid Smoke and 2% EM4, and P3: Concentration of 2% Liquid Smoke and EM4 2%. Physical quality was obtained by organoleptic testing involving 20 respondents with texture, color and aroma parameters, as well as pH testing, while chemical quality was obtained by proximate testing consisting of; BK, KA, SK, PK and BETN. The observation data and analysis results were tested using the One Way Anova statistical test method and the Duncan test with SPSS 25. The addition of liquid smoke additives reduced the percentage of mold and improved the physical quality of color in corn plant silage. and produces the same physical quality by administering the EM4 additive or a combination thereof. It is necessary to carry out further tests in the form of the Van Soest test to determine the fiber fraction and in vitro testing to determine the digestibility and fermentation quality of corn silage.